Deformation within an exposed salt wall: Recumbent folding and extrusion of evaporites in the Dead Sea Basin. (January 2015) - Alsop, G.I.; Weinberger, R.; Levi, T.; Marco, S.
Abstract: Despite the enormous global interest in salt tectonics, which is largely driven by its importance to hydrocarbon exploration, direct field-based studies of salt exposed at the Earth's surface are rare. However, Mount Sedom, located at the western side of the Dead Sea Basin, presents one such opportunity for detailed analysis of salt and the associated sedimentary and structural record of its movement. The Sedom salt wall is a 10 km × 1.5 km N–S trending ridge comprising a range of Late Miocene-Pliocene evaporites and clastics, which have penetrated the overlying Pleistocene clastic sequence. The salt wall displays a moderate-steep west dipping western margin and an overturned (west-dipping) eastern flank. The sedimentary record of passive wall growth includes sedimentary breccia horizons that locally truncate underlying beds and are interpreted to reflect sediments having been shed off the crest of the growing salt wall. Structurally, the overturned eastern flank is marked by upturn within the overburden, extending for >300 m from the salt wall. Deformation within the evaporites is characterised by ductile folding and boudinage, while a 200 m thick clastic unit within the salt wall forms a tight recumbent fold traceable for 5 km along strike and associated with a 500 m wide inverted limb. This overturned gently-dipping limb is marked by NE-directed folding and thrusting, sedimentary injections, and a remarkable attenuation of the underlying salt from ∼380 m to <20 m over just 200 m of strike length. The inverted limb is overlain by an undeformed anhydrite, gypsum and clastics caprock, thought to be the residue from a now dissolved salt sheet that extruded over the top of the fold. Expulsion of salt down the regional slope towards the NE, combined with subsequent dissolution of evaporites, may have resulted in local 'pinching shut' of the salt wall, leading to a distinctive hour-glass map pattern. This area also coincides with deposition of a thicker overlying clastic sequence, indicating continued subsidence of this part of the salt wall. Our detailed fieldwork forms the first direct observation and description of large recumbent folds within salt walls, and permits analysis below the limits of seismic resolution. It thereby allows more rigorous testing of salt tectonic models and mechanisms. Graphical abstract: Highlights: The Sedom salt wall on the margin of the Dead Sea is a well exposed Pliocene evaporite diapir. Evaporites were extruded from the salt wall and underwent gravity-driven flow towards the depocentre of the basin. We provide the first direct field study of km-scale recumbent folding within an exposed salt wall. Km-scale overturned folds are generated through salt expulsion and high fluid pressures associated with a rolling fold hinge.